Effect of V-box Insertion Position on Hormone Response Activity of GWSF Promoter in Capsicum annuum - Shuyuan YANG; Lijun CHEN; Min XU; Meizhu WU; Zhenchi HUANG (Guangdong nongye kexue, 2025)
【Objective】The ideal artificial promoter can precisely regulate the spatiotemporal expression of genes for crop genetic improvement. V-box element was introduced at different positions within GWSF, an ideal plant pathogeninducible promoter, to investigate the positional effects of new elements and provide a reference for the design and application of synthetic promoters.【Method】The dimer of the V-box element was introduced into the upstream, midstream, and downstream position of the GWSF promoter, and the three modified promoters were subsequently named VGWSF, GWVSF, and GWSFV according to their respective insertion positions. These promoters were used to replace the CaMV35S (cauliflower mosaic virus 35S) promoter in the plasmid pBI121 to control the expression of β-glucuronidase (gus) gene. The recombinant plasmids were transformed into Agrobacterium tumefaciens GV3101. The leaf discs of Capsicum annuum were transient transformed using the Agrobacterium-mediated method. After 12 h, the transformed leaf discs were treated with abscisic acid, salicylic acid, or ethylene for another 12 h. The inducible transcriptional levels of modified promoters were detected by GUS staining and realtime quantitative PCR (qPCR).【Result】Compared with the original promoter GWSF, the basal transcription levels of the three improved promoters (VGWSF, GWVSF, GWSFV) significantly increased. Normalized the transcription level of CaMV35S as 1, the basal transcription level of GWSF was 0.190, while those of VGWSF, GWVSF, and GWSFV were 3.348, 2.503, and 0.953, respectively, which were 17.613-fold, 13.165-fold, and 5.011-fold higher than the original promoter. Under ABA induction, the transcription levels of the three improved promoters were all higher than their basal levels: VGWSF reached 12.309 after induction (3.676-fold of the basal level), GWVSF was 4.783 (1.911-fold), and GWSFV was 5.405 (5.674-fold). After SA treatment, the transcription levels of VGWSF and GWVSF decreased to 0.502 and 0.244, respectively, an 85% and 90% decrease from their basal levels, while GWSFV increased to 2.464. After ethephon treatment, the transcriptional activity of the three improved promoters was inhibited, with transcription levels all below 0.520.【Conclusion】The basal transcription level of the modified promoters increased with the introduction of V-box. The basal transcription level of GWSFV was relatively low, and its transcriptional activity increased significantly when being induced by ABA or SA. The position of the V-box had a significant impact on the transcriptional characteristics of the original promoter.